Outpatient administration of Ifosfamide-Etoposide in a Cohort of Pediatric Sarcoma Patients: A Single Cancer Center Experience in Jordan - Yaser, Sameer; Sultan, Iyad; Halalsheh, Hadeel; Albtoush, Omar M; Jaffal, Jaafar; Shehadeh, Ahmad; Abdelal, Samer; Jaber, Omar; Asha, Wafaa; Hijlih, Ramiz Abu; et al. (Archives of Clinical and Medical Case Reports, 2025)
The standard Ifosfamide-Etoposide (IE) regimen is typically administered in an inpatient setting. This study aimed to report our experience using outpatient administration in terms of safety and the potentiality of cost-reduction. A retrospective chart review was conducted for all pediatric patients diagnosed with any primitive neuroectodermal tumor (PNET) who had received outpatient Ifosfamide-Etoposide chemotherapy at KHCC in Jordan between 2007 and 2014. We evaluated the associated toxicity resulting from their treatment and compared the average treatment cost of the selected cases to the average cost of treatment for a comparable group of patients who received IE inside the hospital. Forty-eight patients were included, Forty-six were Ewing's sarcoma, and two patients were Rhabdomyosarcoma. Their toxicity profile revealed an overall tolerable profile; only three patients presented with hemorrhagic cystitis, and no toxic deaths were reported. The most common side-effect was grade 3-4 neutropenia (54% of the patients demonstrated it). Compliance with the urinalysis testing was found to be relatively low; 12% were submitted on time. Treatment cost for outpatients was found to be significantly less than it was for inpatient regimen, with a mean difference of 802.6 JOD (1132 USD) per cycle of Ifosfamide-Etoposide (P <0.001). The Outpatient Ifosfamide administration appears to be feasible and safe. It had a significant impact on cutting the cost. A structured prospective study is needed to confirm these findings. More focus is required on outpatient IE administration's effect on the quality of life and the methods to optimize adherence to study protocol, particularly in urinalysis testing.